Agronomic Characteristics of Various Soybean Varieties (Glycine max L.) Can Grow and Produce Due to Shade Stress - Deddy Wahyudin Purba; Suswati Suswati; Zoelhery Noer (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Soybeans are the main food crop commodity in Indonesia which is ranked third after rice and corn. The aim of this research is to determine the characteristics of soybean varieties that are able to grow and produce due to shade stress. The research was carried out from November 2023 to February 2024. The research used a Factorial Randomized Group Design (RAK). with the first 2 treatment factors Shading Stress, including P0 = No shade, P1 = TBM and P2 = TM. The second factor is the variation in soybean varieties consisting of six levels including (V1) Mutiara 1, (V2) Agromulyo, (V3) Dena 1, (V4) Dena 2, (V5) Edamame and (V6) Devon 1. Observed parameters include plant height, leaf area index, number of pithy pods and harvest age. Research data was analyzed using the ANOVA variance analysis procedure to determine whether there was an effect of each treatment. The results showed that the effect of TBM shading (P1) could increase plant height (48.18 cm), and treatment without shading (P0) increased the number of pithy pods (45.66 pods). The effect of varietal variations shows that the best performance is the Edamame (V5) variety on plant height (49.64 cm), Dena 2 (V4) produces the highest number of pods (40.62 pods), and Agromulyo (V2) produces the highest harvest age (83 days). Analysis of shade and various varieties that were carefully assessed on the growth and yield of soybean production showed that it had no real influence on all the parameters observed.